Effect of Transformational Leadership and Organizational Citizenship Behavior: Determining the Roles of Supervisor Identification, and Self-determination in the Automobile Industry - Zheng, Zhou; Segumpan, Reynaldo Gacho (South Asian Journal of Social Sciences and Humanities, 2024)
Background and Purpose: The present study analyses the impact of transformational (TL),  transactional (TRL) and laissez-faire styles (LSF) of leadership on Organizational Citizenship  Behavior (OCB) of employees in the context of the automobile industry. Moreover, the study  also focuses on the mediating effect of self-determination (SDE) and the moderating role of  supervisor identification (SD) on the proposed correlation. Method: The primary data for the  study was collected by designing a survey questionnaire. The questionnaires were distributed  among the employees from the automobile industry and a final sample of 312 responses was  utilized. The data was analyzed through the application of PLS-SEM. Findings: The study  validated a positive and significant relationship between LSF and OCB. Similarly, TRL and  OCB were positively and significantly related. Notably, TL was an insignificant predictor of  OCB. SD exerted a significant moderating role in the association between TRL and SDE only.  The evaluation of the mediating role of SDE in the association between leadership styles and  OCB revealed that SDE significantly mediated the association between TL and OCB, and TRL  and OCB. Nevertheless, SDE was an insignificant mediator in the association between LSF  and OCB. Conclusion and Implications: Thus, the findings of the present study hold  significance for leaders from automobile industry leaders and offer guidance to design  strategies for enhancing the OCB and workplace engagement through effective leadership  strategies.
Keywords: Transformational leadership; Organizational citizenship behavior; Leadership styles; Supervisor identification; Self-determination